ANALISIS FAKTOR PENYEBAB GURU PAI KURANG MEMILIKI KOMPETENSI PROFESIONAL DALAM MENGAJAR DAN UPAYA MENGATASINYA (STUDI KASUS DI MI DARUL ULUM MADIUN) - Lau Han Sein; Nehru Millat Ahmad (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
The purpose of this study was to determine the factors that caused PAI teachers at MI Darul Ulum Madiun to lack academic competence and efforts to overcome them. This study uses descriptive research methods to determine the factors that affect the professional competence of teachers. Data collection techniques in this study used observation, interviews, and also documentation. The results of this study indicate that several factors that influence the professionalism of PAI teachers at MI Darul Ulum Madiun are: First, the teacher recruitment system is less professional. Second, many PAI teachers teach not according to their academic qualifications so that their understanding of PAI material is still not deep. Third, the teacher's lack of motivation in developing his personal qualities. Of the several factors causing the lack of professionalism of PAI teachers at MI Darul Ulum Madiun, the solution that can be done is to improve the management of the school, such as in the problem of recruiting new educators that are designed and implemented properly according to what is needed, starting from making staff recruitments. interesting new applications, filing, and also a professional selection stage so that the teachers who will be recruited are truly competent and ready to carry out their duties properly. The school prefers to choose PAI teachers, because the burden of PAI teachers is much greater than that of non-PAI teachers, so there needs to be teachers who are competent in especially religious matters.Keywords: Professional Competence, Teachers, PAI